2015
DOI: 10.1136/bmj.h4863
|View full text |Cite
|
Sign up to set email alerts
|

Evidence about electronic cigarettes: a foundation built on rock or sand?

Abstract: Public Health England recently endorsed the use of e-cigarettes as an aid to quitting smoking. Martin McKee and Simon Capewell question the evidence on safety and efficacy underpinning the recommendations

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
65
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 11 publications
0
65
0
1
Order By: Relevance
“…There is significant debate around the individual and population implications of e-cigarette use [39][40][41][42][43][44][45] . Our study is not without limitations.…”
Section: Discussionmentioning
confidence: 99%
“…There is significant debate around the individual and population implications of e-cigarette use [39][40][41][42][43][44][45] . Our study is not without limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps surprisingly, in the context of lack of robustness from available data, Public Health England reported overwhelmingly in favor of the use of e-cigarettes, citing that they were 95% less harmful than smoking. 21 However, this report has been criticized for the lack of critical appraisal of the empirical evidence, 22,23 and recent systematic reviews and meta-analyses of real-world clinical scenarios are less supportive of the effectiveness of e-cigarettes. 24 We currently have no data on the use of e-cigarettes in the setting of solid-organ transplant, and further clarification is warranted before robust recommendations can be made for the use of safe and effective smoking cessation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…The author concerned recently co-authored a paper with a company employee [12]. Little is known about the study funder, although other companies registered at the same address are reported to have connections to BAT [11]. Another organization described in the paper as supporting this research, with which an individual with previous tobacco company funding plays a leading role, has also been claimed to be linked to a tobacco company [13].…”
Section: Ethical Issues Raised By Tobacco Industry-linked Research Inmentioning
confidence: 99%
“…A paper by Nutt and colleagues [9] is cited a number of times in the paper by Shaw and colleagues to provide evidence promoting the public health potential of e-cigarettes. This study has been controversial [10,11], partly as no tobacco industry funding was declared, and yet some authors have had financial links with tobacco companies in the past [11].…”
Section: Ethical Issues Raised By Tobacco Industry-linked Research Inmentioning
confidence: 99%
See 1 more Smart Citation